Gender Differences in Creative Thinking Skills and Learning Achievement Through Guided Discovery Learning Assisted by PhET Simulation - Baiq Nabila Saufika Zainuri; Syahrial Ayub (Indonesian Publication Center, 2022)
This study aims to analyze differences in students’ creative thinking abilities and academic achievement based on gender through the application of the Guided Discovery Learning model aided by PhET Simulations. The study employed a quantitative approach with a one-group pretest–posttest pre-experimental design combined with a comparative analysis based on gender. The sample consisted of 20 10th-grade science students, including 8 male students and 12 female students. The research instruments comprised a creative thinking ability test and an academic achievement test. Data were analyzed using the Shapiro-Wilk normality test and the Mann-Whitney U test. The results showed that there were no significant differences between male and female students in creative thinking ability (Sig = 0.251) or academic achievement (Sig = 0.842). These findings indicate that the learning model used has an equal impact on both gender groups, thereby having the potential to create inclusive and gender-neutral learning.